STUDI LITERATUR MEDIA DIGITAL DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Budiarti, Dina; Rohani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of using digital media on enhancing critical thinking skills among elementary school students. The method used in this research is a literature review,which involves collecting and processing data from existing studies. The data were obtained from several articles sourced from google, google scholar, and other websites, covering the years 2020-2025. The data were analyzed through reduction and presentation techniques. The analysis revealed that various types of digital media can be utilized to improve students critical thingking skills, as such as I-spiring, mapping-based e-book, animated learning videos, educational games, flipbook andword walls.There learning media stimulate students critical hingking abilities in engaging and interactive ways.